2013
DOI: 10.1093/jac/dkt259
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of OXA-48 carbapenemase-producing Escherichia coli and Klebsiella pneumoniae in dogs

Abstract: This is the first known report of OXA-48-producing bacteria from companion animals. The clonal nature of the K. pneumoniae and two E. coli isolates suggests a nosocomial dissemination rather than repeated introduction by individual patients into the clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
98
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(115 citation statements)
references
References 38 publications
6
98
2
4
Order By: Relevance
“…Hence, almost 20% of the owners considered here (including family members) could be at risk of acquiring these genes from their dogs. Moreover, in contrast to a recent report in diseased dogs in Germany (23), no carbapenemase producer was found. However, ChromID ESBL plates may have been impaired in detecting certain phenotypes, such as OXA-48 producers in the absence of ESBL coexpression.…”
Section: Resultscontrasting
confidence: 99%
“…Hence, almost 20% of the owners considered here (including family members) could be at risk of acquiring these genes from their dogs. Moreover, in contrast to a recent report in diseased dogs in Germany (23), no carbapenemase producer was found. However, ChromID ESBL plates may have been impaired in detecting certain phenotypes, such as OXA-48 producers in the absence of ESBL coexpression.…”
Section: Resultscontrasting
confidence: 99%
“…The same study identified, ESBL producing S. enterica, Proteus miriabilis and Enterobacter cloaceae from urinary, wound, respiratory, abdominal and bone infections (Dierikx et al, 2012). In Germany from six nosocomially infected dogs, OXA-48 type Carbopenamases producing E. coli and K. pneumonia were isolated (Stolle et al, 2013) and in France CTX-M-15 generating K. pneumoniae have been detected from urinary tract infections of dogs and cats (Haenni et al, 2012). Clinical samples from urinary, wound infections etc.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 86%
“…During the past few years, cases of infections caused by K. pneumoniae strains resistant to clinically important classes of antibiotics, including third-generation cephalosporins (3GCs), have also been reported in companion animals (2)(3)(4)(5)(6). 3GCs represent important antibiotics for the treatment of serious infections caused by K. pneumoniae before the use of last-resort carbapenems.…”
mentioning
confidence: 99%